Local atomic arrangement of melts Al — Fe 20 at. % — Sn MELTS - Яковенко, Олексій Михайлович; Роїк Олександр Сергійович; Каширіна, Ярослава (Київський національний університет імені Тараса Шевченка, 2025)
Background. Alloying of the aluminum-based antifriction materials enhances the wear resistance and thermal stability. Copper, cobalt, and chromium are widely used in the industry as additions to aluminum–tin alloys; however, there are no studies on the influence of iron in the scientific literature. The determination of the peculiarities of atomic ordering in Al–Fe–Sn melts should allow to predict the phase composition of the corresponding composites. Methods. The scattering curves of Al67Fe20Sn13, Al60Fe20Sn20 and Al52Fe20Sn20 melts have been obtained at 1500°C by means of X-ray diffraction. The structural models of melts have been reconstructed using Reverse Monte Carlo simulation, and statistical-geometric approach with Voronoi diagrams and Delaunay tessellations was applied for characterization. Results. The micro-inhomogeneous structure of Al80-xFe20Snx (x=13, 20, 28) melts at 1500°C was confirmed. After the analysis of the obtained structural models, the regularities of changes in the local environment of atoms with concentration were established. Conclusions. The possibility of the existence of the enriched in Fe and Sn phases in the aluminum matrix after solidification of the Al80-xFe20Snx alloys with low tin content has been demonstrated. Such phases have a negative impact on the operational characteristics of antifriction materials, therefore the compositions Al60Fe20Sn20 and Al52Fe20Sn28 are more preferable.

Вступ. Легування антифрикційних сплавів на основі алюмінію дозволяє підвищити зносостійкість та термічну стабільність. У промисловості вже широко використовуються мідь, кобальт, хром як добавки до алюмінієво-олов’яних сплавів, але у науковій літературі відсутні роботи щодо впливу заліза. Встановлення закономірностей атомного впорядкування у розплавах Al-Fe-Sn дозволить спрогнозувати фазовий склад відповідних композитів. Методи. Було отримано криві розсіювання рентгенівського випромінювання розплавів складу Al67Fe20Sn13, Al60Fe20Sn20 та Al52Fe20Sn28 при 1500°С. Проведено реконструкцію структурних моделей розплавів за допомогою методу оберненого Монте Карло, для характеристики яких застосовано статистично-геометричний метод Вороного-Делоне. Результати. Підтверджено мікронеоднорідну будову розплавів Al80-xFe20Snx (x=13, 20, 28) при 1500°С. Завдяки аналізу отриманих структурних моделей встановлено закономірності локального оточення атомів із зміною концентрації. Висновки. Показано, що при низькому вмісті олова для сплавів Al80-xFe20Snx при охолодженні розплаву можливе отримання збагачених на Fe та Sn фаз в алюмінієвій матриці, що погіршуватиме експлуатаційні характеристики антифрикційних матеріалів, у зв’язку з чим рекомендовано використовувати склади Al60Fe20Sn20 та Al52Fe20Sn28.
Локальне атомне впорядкування розплавів Al — Fe 20 ат.% — Sn
Keywords: рентгенівська дифракція; металічний розплав; метод оберненого Монте Карло; ближній порядок; X-ray diffraction; metallic melt; Reverse Monte Carlo simulation; short range order